FAKTOR - FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK PADA MASA PANDEMI (STUDI KASUS UMKM KABUPATEN SOPPENG). - Ariaty Arfah, Eka; Arfah, Dwi Astuty (Restitusi : Jurnal Riset Perpajakan, 2022)
This study aims to analyze the factors that influence mandatory compliance during the current pandemic for MSMEs in Soppeng Regency. These factors include knowledge of taxation, tax policies, attitudes, tax authorities, and the implementation of a self-assessment system. The research method used is quantitative with primary data, namely distributing 92 questionnaires to taxpayers. The method of data analysis used in this study is multiple linear regression analysis. The results of this study indicate that tax knowledge, tax policies, attitudes, tax authorities and the implementation of a self-assessment system have a positive and significant effect on taxpayer compliance. In the sense that if these factors are applied in an increasing and adequate manner, then taxpayer compliance will also increase towards MSMEs in Soppeng Regency.